Detecção de soro lácteo por cromatografia líquida de alta eficiência em amostras de leite cru conservadas com bronopol - Moisa Medeiros Lasmar (2007)
The objective of this study was to evaluate the viability of the use of raw milk samples conserved with bronopol in the detection of cheese whey by High Performance Liquid Chromatography (HPLC). The samples added with bronopol were stored in two temperatures (7 and 30º C) and the control samples (without preservative) were kept under freezing. All the groups were tested for the time of storage up to eight days. In each group were added five levels of cheese whey (0%, 2%, 5%, 10% and 20%). There was no difference (p > 0.05) among the treatments thus, it is possible to use samples of raw milk conserved with bronopol in the detection of cheese whey by HPLC. The storage time and temperature did not interfere in this methodology for samples conserved with bronopol stored cooled or at room temperature up to eight days